THEME: LANGUAGE ACQUISITION THEORIES - Safarova Dildora,; Mirxamidova Madina,; Quvanova Mohinur, (Ustozlar uchun, 2025)
Language acquisition is a fundamental aspect of human cognition, studied through various theories. This article explores key perspectives, including behaviorism, nativism, and interactionism, analyzing their strengths and limitations. The role of social and cognitive factors, as well as critical periods for language learning, is also examined. Understanding these theories helps educators and linguists develop effective teaching methods. By comparing these approaches, the paper highlights the complexities of language development and the interplay between innate abilities and environmental influences.